Ibn Khaldun's Logical Thinking in Hacking Islamic Philosophy - Muhammad Faishal (Program Pascasarjana UIN Sumatera Utara, 2023)
This study aims to explore the contribution of Ibn Khaldun in the development of Islamic philosophical thought, especially in the context of logic. The research method used is descriptive analysis with a qualitative approach. This research analysis of Ibn Khaldun's views on logic, truth testing, argumentation, and the role of science in religion. The results showed that Ibn Khaldun's concepts remain relevant in Islamic philosophical thought today, especially in the context of scientific research and dialogue between religion and science. This research provides an in-depth look at the critical role of Ibn Khaldun in the development of logical thinking in Islamic philosophy. Tujuan penelitian ini adalah untuk menggali kontribusi Ibnu Khaldun dalam pengembangan pemikiran filsafat Islam, terutama dalam konteks ilmu logika. Metode penelitian yang digunakan adalah analisis deskriptif dengan pendekatan kualitatif. Penelitian ini menganalisis pandangan Ibnu Khaldun tentang logika, pengujian kebenaran, argumentasi, serta peran ilmu pengetahuan dalam agama. Hasil penelitian menunjukkan bahwa konsep-konsep Ibnu Khaldun tetap relevan dalam pemikiran filsafat Islam saat ini, terutama dalam konteks penelitian ilmiah dan dialog antara agama dan ilmu pengetahuan. Penelitian ini memberikan pandangan yang mendalam tentang peran penting Ibnu Khaldun dalam pengembangan pemikiran logis dalam filsafat Islam.